2022
DOI: 10.3390/cancers14041030
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characterization of KRAS G12C-Mutated Lung Adenocarcinomas

Abstract: Lung adenocarcinoma (LUAD) is the major subtype of non-small cell lung cancer, accounting for approximately 60% of cases. Molecular analysis of LUADs showed that the KRAS gene is mutated in up to 30% of cases; such cases were previously considered “undruggable”. The KRAS G12C mutation has become a hot topic of research after initial, promising, phase I and II trials with targeted inhibitors. We analyzed the morphological and genomic landscape of 202 KRAS G12C mutated LUADs using next-generation sequencing, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The higher proportion of females in the KRAS G12C group is in concordance with some recent studies [22][23][24][25][26], but not all identified studies [26][27][28][29][30]. It is well established that KRAS G12C is associated with smoking and that non-squamous cell carcinoma is the most frequent histological subtype [30].…”
Section: Discussionsupporting
confidence: 88%
“…The higher proportion of females in the KRAS G12C group is in concordance with some recent studies [22][23][24][25][26], but not all identified studies [26][27][28][29][30]. It is well established that KRAS G12C is associated with smoking and that non-squamous cell carcinoma is the most frequent histological subtype [30].…”
Section: Discussionsupporting
confidence: 88%
“…Heterogeneity can lead to a decrease in sensitivity to individualized treatment methods. The use of next-generation sequencing techniques greatly facilitates understanding the genetic and epigenetic basis of cancer and its heterogeneity [13]. Intratumoral heterogeneity and different responses to treatment represent a current challenge in the development of targeted therapies in lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…STK11 mutational inactivation has been associated with a ‘cold’ tumour immune microenvironment with fewer infiltrating T lymphocytes and could represent a major driver to primary resistance to ICI in KRAS -mutated adenocarcinomas 51. Adenocarcinomas with concomitant KRAS p.G12C and STK11 mutations might benefit from the new KRAS G12C inhibitors potentially combined with ICI 52. In contrast, TP53 mutations have been associated with a prominent inflammatory response with increased amount of infiltrating T lymphocytes which could make it susceptible to treatment with ICI 17 26.…”
Section: Discussionmentioning
confidence: 99%